2016
DOI: 10.1186/s40064-016-3020-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and implementation of QR Code Identity Tag system for Healthcare in Turkey

Abstract: For this study, we designed a QR Code Identity Tag system to integrate into the Turkish healthcare system. This system provides QR code-based medical identification alerts and an in-hospital patient identification system. Every member of the medical system is assigned a unique QR Code Tag; to facilitate medical identification alerts, the QR Code Identity Tag can be worn as a bracelet or necklace or carried as an ID card. Patients must always possess the QR Code Identity bracelets within hospital grounds. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Tested as potentially linkable to any database with infinite possibilities of linking to all types of documents (dental charts, radiographs, photographs, videos, contact phones, etc. ), QR codes could be implemented as a system of marking at an institutional level (such as a university dental clinic, for example) that allows the control and accessibility of the information under the confidentiality protection of the current Chilean legal norms. However, this research has only sought to emphasize the perceptions of the carriers of the dentures, their fears, their demands, and, regardless of what type of system they use, call attention to the incredible opportunity to operationally implement some type of system since the individuals are receptive to this.…”
Section: Discussionmentioning
confidence: 99%
“…Tested as potentially linkable to any database with infinite possibilities of linking to all types of documents (dental charts, radiographs, photographs, videos, contact phones, etc. ), QR codes could be implemented as a system of marking at an institutional level (such as a university dental clinic, for example) that allows the control and accessibility of the information under the confidentiality protection of the current Chilean legal norms. However, this research has only sought to emphasize the perceptions of the carriers of the dentures, their fears, their demands, and, regardless of what type of system they use, call attention to the incredible opportunity to operationally implement some type of system since the individuals are receptive to this.…”
Section: Discussionmentioning
confidence: 99%
“…Privacy is not a premium consideration. However, a simple administrative code or QR Code (Uzun & Bilgin, 2016) and social media tracking systems should easily alert the first-line administrators of a medical tourism patient and then conduct the necessary administrative arrangements. Consequently, the data indicates that many patients were waiting for administrators to find out where the patient should go, which does not provide the necessary confidence that the efficacy of the arrangements for service quality provision were adequate (Owusu-Frimpong, Nwankwo & Dason, 2010).…”
Section: Health Services Unit Internal Managementmentioning
confidence: 99%
“…The data indicated that in-house tracking of patients was conducted by some service providers through bar-codes entered into the service providers internal system. For example, the use of a QR Code tag system and a smartphone (including 2D information codes) (Uzun & Bilgin, 2016). This helped develop a normalised internal patient tracking process from first-meet -and also ensure triangulation of ID sources to corroborate a patient's ID as well as medicine concerns, attempts at language conciliation and food requirements.…”
Section: Services Marketing Developmentsmentioning
confidence: 99%
“…In medical field, QR codes can be used in health information; radiographic records [16]; medical records and information management [17][18][19][20]; patient recognition [21][22][23]; creation of patient resources [24]; medical presentations [25]; and the recognition of medications, pharmaceutical products, equipment and devices.…”
Section: Barcodementioning
confidence: 99%